Ekstraksi Polifenol Total dari Herba Suruhan (Peperomia pellucida [L.] KUNTH) Menggunakan Metode Citric Acid-Glucose Based Microwave Assisted Extraction - Sabaniah; Duwi Meiliyani; Islamudin Ahmad (Proceeding of Mulawarman Pharmaceuticals Conferences, 2019)
This study aims to determine the effect of citric acid-glucose based microwave assited extraction (MAE) method on total polyphenols content from (Peperomia pellucida [L.] Kunth) herbs. Dried samples were extracted using green solvent glucose citric acid with a ratio of 1: 1 g/g, 3: 1 g/g, and 5: 1 g/g, respectively, 30% microwave power for 5 minutes, and 1:5 g /mL solid-liquid ratio. Then the obtained extract solution was performed determination total polyphenols content using Folin-Ciocalteu reagent, and the absorbance was measured using a UV-Vis spectrophotometer at 791 nm. Based on the results, obtained total polyphenols content according to the extraction condition namely 214.405 mg GAE/g sample (3: 1 g /g solvent), 84.833 mg GAE /g sample (1: 1 g /g solvent) and 53,9451 mg GAE/g sample (5: 1 g /g solvent), respectively. This study is a preliminary data about the use of citric acid-glucose based microwave assisted extraction method on total polyphenols content from this plant quickly, easily and efficiently.